Effects of choice feeding on the performance of village chicken after the peak of egg production - A. H., Ramlah; H., Mohd Husni; A. H., Sarinah (Asian-Australasian Association of Animal Production Societies, 1994)
An experiment was carried out with village chicken at the laying stage raised on the semi-intensive system on three feeding treatments with each of 30 birds replicated three times. The three feeding treatments were: layer mash only, layer mash and corn as choices and choices of a high protein concentrate and corn. Feed and protein intake was significantly higher for birds on the layer mash and lower for birds on the choices of a high protein and corn diet. There was no differences in egg production for the birds fed the layer mash either alone or a choice with corn but lower for the birds on the choices of a high protein feed and corn. There was no differences in egg weight and gross efficiency for all treatments. The practice of choice feeding layer mash and corn could be adopted by farmers rearing village chicken under the semi-intensive system due to the lower cost.